2011
DOI: 10.1186/1748-717x-6-152
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric modulated arc planning for lung stereotactic body radiotherapy using conventional and unflattened photon beams: a dosimetric comparison with 3D technique

Abstract: PurposeFrequently, three-dimensional (3D) conformal beams are used in lung cancer stereotactic body radiotherapy (SBRT). Recently, volumetric modulated arc therapy (VMAT) was introduced as a new treatment modality. VMAT techniques shorten delivery time, reducing the possibility of intrafraction target motion. However dose distributions can be quite different from standard 3D therapy. This study quantifies those differences, with focus on VMAT plans using unflattened photon beams.MethodsA total of 15 lung cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
78
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 27 publications
(29 reference statements)
8
78
2
Order By: Relevance
“…Yamashita, et al already reported details of treatment from our hospital (20). VMAT has been reported to be a novel rotational technique and an extension of IMRT, and is applicable for SBRT for lung tumors (23,(30)(31)(32)(33)(34). By introducing VMAT, we could reduce the dose delivery time down to 210 sec for a D95 prescription dose of 50 Gy in four fractions (35).…”
Section: Discussionmentioning
confidence: 99%
“…Yamashita, et al already reported details of treatment from our hospital (20). VMAT has been reported to be a novel rotational technique and an extension of IMRT, and is applicable for SBRT for lung tumors (23,(30)(31)(32)(33)(34). By introducing VMAT, we could reduce the dose delivery time down to 210 sec for a D95 prescription dose of 50 Gy in four fractions (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, conventional linacs allow caudal arcs to be used to some extent, although the available geometric freedom is less than that of the vero4DRT. We used a conventional linac (the Clinac iX; Varian Medical Systems, Palo Alto, CA) to experimentally explore how much angle could safely be assumed in the context of caudal arcs, In agreement with the literature, (20) the range was maximally 5°. Next, we replanned three representative plans within this range of angle (the plans were termed Plans C).…”
Section: Discussionmentioning
confidence: 73%
“…In addition, an IMRT plan is able to reduce the irradiated dose of lung normal tissue compared with a 3D-CRT plan. Zhang et al 18 and Ong et al 19 reported better conformity for tumours and lower doses for risk organ in VMAT compared with those in 3D-CRT. These results indicated the improved value of dosimetric parameters adding intensity modulation to SBRT for earlystage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have demonstrated the superiority of dosimetric parameters in IMRT plans compared with those in 3D-CRT plans. [18][19][20] Liu et al 20 reported a treatment planning study of ten patients with lung cancer, showing that the CI and HI values in the IMRT plan were significantly superior to those in the 3D-CRT plan. In addition, an IMRT plan is able to reduce the irradiated dose of lung normal tissue compared with a 3D-CRT plan.…”
Section: Discussionmentioning
confidence: 99%